Pemanfaatan Lahan Sempit Sebagai Tempat Budidaya Ikan Cupang di Mertasinga, Cilacap - Oto Prasadi (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
Betta splendens is an ornamental fish of economic value, this fish has the excellence color, fight instinct, and short life cycle. Betta fish into the category is easy to cultivate (narrow field). Betta splendens are one of 70 species of betta fish (Betta sp.) experienced breeding. The process begin several characters from body color, size and fin shape for ornamental and fight purposes. This potential can be implemented and developed to new breeders in members of breeder cilacap community, so as to improve the quality and quantity of betta fish. Existing problems i.e., how to optimize the unproductive narrow land more productive narrow land for the cultivation of betta fish and addition knowledges of betta cultivation, especially new breeders. This program 2 groups of citizens and 1 group of students. The solution provided, i.e., discussion about prospect of betta cultivation and focused training starting from selection of broodstock, process of breeding, egg and larvae breeding and feeding. The results from this activity is the use of land for the cultivation and the success of the spawning process new individuals both by citizens and students with entrepreneurship spirit.Sains